Emotional Intelligence among Librarians in Karnataka: An Exploratory Study - Sengupta, Mousumi; Sunil, M. V. (Journal of Information and Knowledge, 2023)
This paper attempts to study ‘Emotional Intelligence’ (EI) to understand the library professionals in the post-covid scenario which has seen technology adoption in library and information services. This study investigates EI among librarians in India by employing the ability model, and administering SSEIT as a research tool. The present study revealed that, in general, the respondents perceive themselves as more or less capable of dealing with situations with EI. However, analysis indicates that respondents differed in perceiving the difficulty and their ability level to tackle a workplace situation with emotional abilities. Data analysis also revealed that respondents with different education level differed significantly in their overall EI scores.